2008
DOI: 10.1103/physrevb.78.064114
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions of cubicGd2O3at high pressures

Abstract: An irreversible structural transformation from the cubic phase to a hexagonal high-pressure phase was verified in Gd 2 O 3 between 7.0 and 15 GPa. The compressibility and bond distances of both phases were determined by the refinement of the x-ray diffraction data. The high-pressure phase of Gd 2 O 3 is 9.2% denser than the cubic phase at 7 GPa. After release of pressure, the high-pressure phase transformed to a monoclinic structure. The pressure-induced phase transition from the monoclinic to the hexagonal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 27 publications
6
57
2
4
Order By: Relevance
“…7 The B to A or A to B transition requires lesser energy as it is displacive type. In this context, it is relevant to mention here that Zhang et al 29 also reported a phase diagram for Gd 2 O 3 according to which at low temperatures, the cubic to hexagonal phase transition is favored with application of pressure while at high temperatures, the monoclinic phase is favored. Since the kinetics of phase transformation depend in general on the pressure, temperature and the amount of non-hydrostatic stresses as well as the existence of defects; the barrier heights for transformation would also depend on these parameters.…”
Section: Resultsmentioning
confidence: 84%
“…7 The B to A or A to B transition requires lesser energy as it is displacive type. In this context, it is relevant to mention here that Zhang et al 29 also reported a phase diagram for Gd 2 O 3 according to which at low temperatures, the cubic to hexagonal phase transition is favored with application of pressure while at high temperatures, the monoclinic phase is favored. Since the kinetics of phase transformation depend in general on the pressure, temperature and the amount of non-hydrostatic stresses as well as the existence of defects; the barrier heights for transformation would also depend on these parameters.…”
Section: Resultsmentioning
confidence: 84%
“…The P-V data up to 12 GPa were fitted to the Birch-Murnaghan equation of state [19] and the bulk modulus and its pressure derivative were found to be: B 0 = 118 ± 21 GPa and B 0 ' =13.9 ± 7.7 respectively [11]. This value of bulk modulus is smaller compared to the reported values of 164, 134 and 188 GPa [15,17,18] with B 0 ' fixed at 4. These values of the bulk moduli are comparable with those reported for other RE 2 O 3 systems [4,[20][21][22].…”
Section: Resultsmentioning
confidence: 73%
“…A recent study on Er-doped Gd 2 O 3 up to ~40 GPa indicated the C→A transition at 8.57-12.5 GPa [15]. However, it [17,18]. The differences in the phase transition behaviour during the return cycle may be due to the difference in the sample quality and the thermal history.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of physical properties on the size opens the way for various applications of Gd 2 O 3 nano particles as protective and corrosive resistant coatings, active additives for the low temperature synthesis of ceramics, grain growth inhibitors, and phase stabiliz ers, as well as in optics (antireflective coatings, thin films for ultraviolet lasers), X ray imaging systems, sensors, nuclear engineering, and other fields of sci ence and technology [8][9][10].…”
Section: Introductionmentioning
confidence: 99%